Pseudoruminococcus massiliensis gen. nov., sp. nov., a new bacterium isolated from the human gut microbiota. (March 2020) - Afouda, P.; Dubourg, G.; Nguyen, T.T.; Raoult, D.; Fournier, P.-E.
Abstract: Pseudoruminococcus massiliensis strain Marseille-P3876 T (= CSUR P3876) is a new genus from the family Ruminococcaceae that was isolated from the gut microbiota of a healthy Senegalese man.